Implementasi Promosi Produk Gadai Melalui Instagram Sebagai Upaya Menarik Minat Nasabah Studi Kasus Pada Pt. Pegadaian Kantor Wilayah IX Jakarta 2 - Annaassya, Adinda Arzeti; Diana, Nana (Peneliti.net, 2024)
This research uses a qualitative method using a descriptive approach through literature studies and interviews. The purpose of this research is to find out the implementation of pawn product promotions carried out by PT Pegadaian Regional Office IX Jakarta 2 through social media in the form of Instagram. The results of this study are the promotions carried out by PT Pegadaian Office Region IX Jakarta 2 through Instagram, namely Cashback, Interest-Free Pawn, Training and Mentoring MSMEs. In addition, to increase awareness of PT Pegadaian, there is a webinar program for entrepreneurs who want to start their business. Promotion of pawn products is carried out every other day with two to three contents in one upload.